PENEGAKAN HUKUM KEGIATAN PENGANGKUTAN DAN PENYIMPANAN BBM TANPA IZIN USAHA DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PALANGKARAYA - Ronaldi Ronaldi (MORALITY: Jurnal Ilmu Hukum, 2020)
Based on studies conducted, every increase in world oil prices causes diesel queues because the price margins between subsidized and non-subsidized fuels have increased relatively larger than before. This price disparity triggers the existence of illegal fuel sellers caused by the resistance of the industrial sector to buy non-subsidized diesel fuel in consideration of an increase in operational costs. In an effort to control inflation, several problems have been identified, namely the presence of illegal fuel sellers, fuel hoarders / storers without permits that arise due to utilizing the momentum to sell fuel at a higher price at the retail level, causing a long queue at gas stations. The existence of illegal fuel sellers, fuel hoarders / depositors without permits who abuse fuel becomes a major problem especially in the City of Palangka Raya. This case, gets serious handling priority from related parties in this case law enforcement officers (Palangkaraya City Police).